(Lack of) Competition, Coordination, and Information Sharing in the Pork Industry: United States, 2009–2020. (March 2023) - Donna, Javier D.; Walsh, Anita N.
In 2020, an antitrust lawsuit was filed against the Pork Integrators alleging a §1 Sherman Act violation. At the center of the Lawsuit, there is an alleged exchange of atomistic information about the Pork integrators' operations using Agri Stats, Inc. as a clearinghouse. We use the Supreme Court benchmark in American Column & Lumber to discuss two questions that arise from the Lawsuit. The first is whether the association of Pork Integrators and Agri Stats, Inc., resulted in the restraint of interstate commerce, the main specific issue at stake in the pork Lawsuit. The second is whether information-exchange agreements using clearinghouses like Agri Stats, Inc., lessen competition and offend U.S. antitrust law, a more general issue beyond the pork Lawsuit. We find that there appears to be ample evidence in the Lawsuit to merit prosecution regarding both trade restraints and information-sharing agreements. We conclude by discussing the role of the Agencies in setting the standards in information-exchange agreements.